Comprehensive molecular characterization of adenoid cystic carcinoma reveals tumor suppressors as novel drivers and prognostic biomarkers - Persson, Marta (2023)
© 2023 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.